Determining The Brand Identity of Setu Babakan In Various Promotional Media As A Betawi Cultural Tourism Destination - Themotia Titi Widaningsih; Fit Yanuar (Indonesian Scientific Publication, 2025)
Proper branding facilitates promotion efforts for managers. Good promotion can increase tourist visits. This study aims to identify branding aspects including brand demographics, personality, character, positioning, name, logo and slogan, ticket prices, and promotional media. The study was conducted in the Betawi cultural tourism area of Setu Babakan, using quantitative research. Data collection was carried out by distributing questionnaires to tourists. Focus group discussions were conducted with managers and the community. The results showed that Setu Babakan tourists were predominantly male, college graduates, both diploma and bachelor's, aged 20-30 years and private sector employees. Tourists utilize social media to obtain tourism information. Setu Babakan visitors are tourists who enjoy traveling and love the beauty of nature and culture.